Odpowiedź :
Odpowiedź:
a. - 3cd
b. 3ax
c. [tex]\frac{1}{2}[/tex][tex]y^{2}[/tex]z
d. [tex]-18cd^{2}[/tex]
e. -[tex]\frac{1}{2}[/tex][tex]a^{2}[/tex][tex]b^{2}[/tex]
f. [tex]10a^{3}[/tex]
reszty nie umiem ale próbowałam pomóc
Szczegółowe wyjaśnienie:
Odpowiedź:
[tex]a)\ \ d\cdot(-3)\cdot x=-3dx\\\\b)\ \ 3(-x)(-a)=3ax\\\\c)\ \ zy\cdot\frac{1}{2}y=\frac{1}{2}y^2z\\\\d)\ \ 2cd\cdot(-9)\cdot d=-18cd\cdot d=-18cd^2\\\\e)\ \ \frac{1}{4}abb\cdot(-2a)=-\frac{2}{4}ab^2\cdot a=-\frac{1}{2}a^2b^2\\\\f)\ \ \frac{1}{2}a^2\cdot4\cdot(-a)\cdot(-5)=2a^2\cdot(-a)\cdot(-5)=-2a^3\cdot(-5)=10a^3\\\\g)\ \ 3x^2y\cdot(-\frac{1}{6}xy)=-\frac{3}{6}x^3y^2=-\frac{1}{2}x^3y^2\\\\h)\ \ -3(-x)(-x)(-y)=3x^2y\\\\i)\ \ 0,2tsts^2\cdot(-15)=-3s^3t^2[/tex]